Serology describes a profile of declining malaria transmission in Farafenni, The Gambia. (December 2015) - van den Hoogen, Lotus; Griffin, Jamie; Cook, Jackie; Sepúlveda, Nuno; Corran, Patrick; Conway, David; Milligan, Paul; Affara, Muna; Allen, Stephen; Proietti, Carla; Ceesay, Serign; Targett, Geoffrey; et al.
Abstract Background Malaria morbidity and mortality has declined in recent years in a number of settings. The ability to describe changes in malaria transmission associated with these declines is important in terms of assessing the potential effects of control interventions, and for monitoring and evaluation purposes. Methods Data from five cross-sectional surveys conducted in Farafenni and surrounding villages on the north bank of River Gambia between 1988 and 2011 were compiled. Antibody responses to MSP-119 were measured in samples from all surveys, data were normalized and expressed as seroprevalence and seroconversion rates (SCR) using different mathematical models. Results Results showed declines in serological metrics with seroprevalence in children aged one to 5 years dropping from 19 % (95 % CI 15–23 %) in 1988 to 1 % (0–2 %) in 2011 (p value for trend in proportions < 0.001) and the SCR dropping from 0.069 year−1 (0.059–0.080) to 0.022 year−1 (0.017–0.028; p = 0.004). The serological data were consistent with previously described drops in both parasite prevalence in children aged 1–5 years (62 %, 57–66 %, in 1988 to 2 %, 0–4 %, in 2011; p < 0.001), and all-cause under five mortality rates (37 per 1000 person-years, 34–41, in 1990 to 17, 15–19, in 2006; p = 0.059). Conclusions This analysis shows accurate reconstruction of historical malaria transmission patterns in the Farafenni area using anti-malarial antibody responses. Demonstrating congruence between serological measures, and conventional clinical and parasitological measures suggests broader utility for serology in monitoring and evaluation of malaria transmission.